Edukasi Rumah Sehat “Door To Door System” Meningkatkan Pengetahuan Sikap dan Perilaku Keluarga Penderita Tb Paru - Sudiadnyana, I Wayan; Yulianti, Anysiah Elly (Poltekkes Kemenkes Denpasar, 2025)
Background: Pulmonary TB disease is still a global health problem. Various prevention efforts have been made, but until now pulmonary TB disease has not been completely treated. Transmission of pulmonary TB disease is influenced by two dominant factors, namely the environment and behavior. The proposed study aims to measure the effectiveness of healthy home education